Boron-Containing heterocycles as promising pharmacological agents. (1st June 2022) - Das, Bhaskar C.; Adil Shareef, Mohammed; Das, Sasmita; Nandwana, Nitesh K.; Das, Yogarupa; Saito, Mariko; Weiss, Louis M.
Graphical abstract: Abstract: The incorporation of the "magic" boron atom has been established as an important new strategy in the field of medicinal chemistry as boron compounds have been shown to form various bonds with their biological targets. Currently, a number of boron-based drugs (e.g. bortezomib, crisaborole, and tavaborole) have been FDA approved and are in the clinic, and several other boron-containing compounds are in clinical trials. Boron-based heterocycles have an incredible potential in the ongoing quest for new therapeutic agents owing to their plethora of biological activities and useful pharmacokinetic profiles. The present perspective is intended to review the pharmacological applications of boron-based heterocycles that have been published. We have classified these compounds into groups exhibiting shared pharmacological activities and discussed their corresponding biological targets focusing mainly on the most potent therapeutic compounds.